2019
DOI: 10.14782/ipsus.539105
|View full text |Cite
|
Sign up to set email alerts
|

Why not Activated? The Temporary Protection Directive and the Mystery of Temporary Protection in the European Union

Abstract: Following the conflicts in former Yugoslavia, temporary protection was introduced as a crucial element of the European Union's (EU) response to refugee crises. The EU even adopted a directive, the Temporary Protection Directive, regarding its implementation. However, despite several refugee crises, it was not activated. Building on a comprehensive analysis of official documents of European institutions and the available secondary literature, this article investigates the main reasons behind its inactivation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Yang et al ( 27 ), Tolsgaard et al ( 24 ), Rutherford-Hemming et al ( 25 ), Kulamakan et al ( 26 ), and Anacleto et al ( 30 ) lost a number of research objects to follow-up, and therefore we must assume a high risk of bias. Setting the issue of uncleared blinded participants aside, all but Rutherford-Hemming et al ( 25 ), Genç and Öner ( 28 ), and Lee et al ( 31 ) did not blind participants; thus, their assessment of outcomes must be regarded as questionable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang et al ( 27 ), Tolsgaard et al ( 24 ), Rutherford-Hemming et al ( 25 ), Kulamakan et al ( 26 ), and Anacleto et al ( 30 ) lost a number of research objects to follow-up, and therefore we must assume a high risk of bias. Setting the issue of uncleared blinded participants aside, all but Rutherford-Hemming et al ( 25 ), Genç and Öner ( 28 ), and Lee et al ( 31 ) did not blind participants; thus, their assessment of outcomes must be regarded as questionable.…”
Section: Resultsmentioning
confidence: 99%
“…Genç and Öner ( 28 ) reported that participants receiving an integrated instructional video performed significantly better on transfer than the procedural-only video. Beattie et al ( 29 ) reported that groups trained in 3D and tested in 3D demonstrated superior training performance and took fewer repetitions to reach proficiency than the group in 2D.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first argument is that the application of the Directive needs a majority in the Council of Ministers that is hard to attain (Commission of the European Communities, 2016b; Genç & Şi̇ri̇n Öner, 2019). Member states that face ‘mass influx’ have an incentive to activate the Directive, but other member states can block the application for political reasons.…”
Section: The Nonapplication Periodmentioning
confidence: 99%
“…For example, Italy and Malta requested to activate the Directive in 2011 when large numbers of refugees from Tunisia and Libya arrived. However, the other member states disputed that this constituted a case of mass influx (Commission of the European Communities, 2016b, p. 13; Genç & Şi̇ri̇n Öner, 2019, p. 8; Gluns & Wessels, 2017, p. 62; Nita, 2013). Similarly, when 50,000 people arrived at the EU's borders with Belarus in 2021, the Commission and some member states did not consider it as a mass influx but framed it as a ‘hybrid attack’ by Belarus (Kienast, 2022).…”
Section: The Nonapplication Periodmentioning
confidence: 99%